The industry-specific relationships between corporate financial performance and 11 corporate social performance dimensions: Taking a more nuanced perspective - Sebastian Rathner (University of Salzburg, Department of Social Sciences and Economics, 2013)
The aim of this paper is to investigate the influence of corporate social performance (CSP) dimensions on corporate financial performance (CFP). It contributes to the literature by exploring a new CSP dataset, by using a more fine-grained CSP measure than prior studies, by explicitly taking industry-specific differences in the CFP-CSP relationship into account and by using an instrumental variable approach to account for endogeneity. 3772 companies out of 10 industry classes are included in the analysis. The results suggest that some CSP dimensions positively influence CFP (e.g. corporate governance) while others impact CFP negatively (e.g. operations). These results remain largely unchanged if endogeneity is taken into account by estimating instrumental variable regressions. Further results show, that the relationships between CSP dimensions and CFP differ by industry class membership.
Keywords: G12; M14; 330; Corporate financial performance; Corporate social performance; Instrumental variable approach